Calcipotriol/betamethasone dipropionate in the treatment of psoriasis vulgaris - Efstratios Vakirlis; Athanasios Kastanis; Demetrios Ioannides (Dove Medical Press, 2008)
Efstratios Vakirlis, Athanasios Kastanis, Demetrios IoannidesA’ Department of Dermatology, Aristotle University of Thessaloniki, GreeceAbstract: Psoriasis is one of the most common skin diseases. The mainstay of treatment for the vast majority of patients is topical therapy. A rising first-line treatment modality for psoriasis vulgaris is the two-compound ointment containing calcipotriol 50 µg/g plus betamethasone dipropionate 0.5 mg/g (Dovobet®, Daivobet®, Taclonex®), which combines a vitamin D analog and a corticosteroid. This innovative formulation preserves the activity and bioavailability of the two components and many clinical studies have demonstrated that it has a greater efficacy, tolerability, and a rapid onset of action compared with its individual ingredients or tacalcitol.Keywords: psoriasis, calcipotriol/betamethasone dipropionate, dovobet, daivobet, taclonex